Alleviation of nickel toxicity in wheat (Triticum aestivum L.) seedlings by selenium supplementation - Gajewska, Ewa; Drobik, Daniel; Wielanek, Marzena; Sekulska-Nalewajko, Joanna; Gocławski, Jarosław; Mazur, Janusz; Skłodowska, Maria (Biological Letters, 2014)
Hydroponically grown wheat seedlings were treated with 50 μM N i and/or 15 μM Se. After a 7-day culture period, their growth parameters, N i, Se, F e, and M g contents, electrolyte leakage, photosynthetic pigment concentrations, and photochemical activity of photosystem II were determined. Exposure of wheat seedlings to N i alone resulted in reduction in the total shoot and root lengths, by 22% and 50%, respectively. Addition of Se to the N i-containing medium significantly improved the growth of these organs, compared to the seedlings subjected to N i alone. Application of Se decreased the accumulation of N i in shoots and roots and partially alleviated the N i-induced decrease in F e and M g concentations in shoots. Electrolyte leakage increased in response to N i stress, but in shoots it was diminished by Se supplementation. Exposure to N i led to a decrease in chlorophyll a and b contents and enhancement of chlorophyll a/b ratio, but did not influence the concentration of carotenoids. Enrichment of the N i-containing medium with Se significantly increased chlorophyll b content, compared to the seedlings treated with N i alone. Photochemical activity, estimated in terms of the maximum quantum yield of photosystem II , decreased in response to N i treatment but was significantly improved by simultaneous addition of Se. Results of our study suggest that alleviation of N i toxicity in wheat seedlings by Se supplementation may be related to limitation of N i uptake.